ANALISIS KINERJA KEUANGAN DIUKUR BERDASARKAN RASIO LIKUIDITAS DAN PROFITABILITAS PADA PT. INDOFOOD SUKSES MAKMUR, TBK - Inayah, Nur; Alwi, Alwi (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
This study aims to analyze the financial performance of PT. Indofood Sukses Makmur, Tbk which is listed on the IDX for the period 2013-2020 through its liquidity and profitability ratios. This research method uses secondary data, namely the annual financial statements of PT. Indofood Sukses Makmur, Tbk for the year 2013-2020 the number of research data is 26. This can be see from the result of the everage ratio as measured by a quick ratio of 1,2 times and the current ratio of 1,5 times which can be said to be less good becaused it is below the industry standard average . The average return on assets of 7% and return on equity of 14% can be said to be not good becaused they arw below the industry standard average